Enhancement in Cathodic Redox Reactions of Single-Chambered Microbial Fuel Cells with Castor Oil-Emitted Powder as Cathode Material - Kumbar, Shobha Suresh; Jadhav, Dipak Ashok; Jarali, Chetan S.; Talange, Dhananjay B.; Afzal, Asif; Khan, Sher Afghan; Asif, Mohammad; Abdullah, Mohd. Zulkifly (MDPI, 2021)
Microbial fuel cell (MFC) would be a standalone solution for clean, sustainable energy and rural electrification. It can be used in addition to wastewater treatment for bioelectricity generation. Materials chosen for the membrane and electrodes are of low cost with suitable conducting ions and electrical properties. The prime objective of the present work is to enhance redox reactions by using novel and low-cost cathode catalysts synthesized from waste castor oil. Synthesized graphene has been used as an anode, castor oil-emitted carbon powder serves as a cathode, and clay material acts as a membrane. Three single-chambered MFC modules developed were used in the current study, and continuous readings were recorded. The maximum voltage achieved was 0.36 V for a 100 mL mixture of domestic wastewater and cow dung for an anodic chamber of 200 mL. The maximum power density obtained was 7280 mW/m2. In addition, a performance test was evaluated for another MFC with inoculums slurry, and a maximum voltage of 0.78 V and power density of 34.4093 mW/m2 with an anodic chamber of 50 mL was reported. The present study’s findings show that such cathode catalysts can be a suitable option for practical applications of microbial fuel cells